Unveiling the impact of green innovation on organizational performance: An empirical study on FMCG sector in Bangladesh - Ashik Das; Md. Shahbub Alam; Md. Rasel Hawlader (goodwood publishing, 2025)
Purpose: This study aims to examine how green innovation affects organizational performance in Bangladesh's fast-moving consumer goods (FMCG) industry. It explores the effects of green product innovation (GPDI) and green process innovation (GPCI) on the financial and non-financial performance of the organizations. Methodology/approach: A quantitative research design was adopted, using a structured questionnaire to collect data from 151 employees working in FMCG companies in Dhaka. Data were analyzed using SPSS through descriptive statistic, reliability analysis, correlation analysis and multiple regression analysis. Results/findings: Multiple regression analysis revealed that both types of green innovation had significant positive relationships with organizational performance metrics. GPDI was found to positively impact financial and non-financial performance. Similarly, GPCI has positive effects on financial and non-financial performance. Conclusion: The study concludes that implementing green innovation strategies is crucial for achieving sustainable competitive advantage in the FMCG sector. Integrating environmental practices in product design and production processes enhances both economic and social dimensions of organizational success. Limitations: The study is limited to only FMCG sector in Bangladesh and also include two dimensions such as green – product and process – innovations. Moreover, it relies solely on quantitative methods, rather than qualitative investigation. Contribution: This study contributes to the existing body of knowledge by empirically validating the Resource-Based View (RBV) theory in explaining how green product and process innovations enhance both financial and non-financial organizational performance. It provides valuable insights for policymakers to integrate eco-friendly strategies that promote long-term organizational resilience in the FMCG sector of Bangladesh.